To what extent does working from home lead to savings in commuting time? A panel analysis using the Australian HILDA Survey - Rüger, Heiko [Verfasser]; Laß, Inga [Verfasser]; Stawarz, Nico [Verfasser]; Mergener, Alexandra [Verfasser] (My University, 2024)
„With growing concern about the climate impact of travel, a central question is the extent to which working from home (WFH) can reduce commuting. Recently, the question has received even more attention as WFH has increased sharply with the onset of the COVID-19 pandemic. However, the state of research is marked by mixed results and lacking longitudinal evidence. We investigate the link between WFH and total weekly commuting time by applying fixed effects regression to panel data from the Australian HILDA Survey, covering the period 2002–2019. We go beyond previous research by examining the moderating roles of the extent of WFH, the duration of the WFH episode, and gender. Overall, we find that doing any work from home is associated with a significant decrease in employees’ weekly commuting time of about 14% on average. The reduction sets in immediately with the start of WFH and tends to further increase thereafter. However, only high shares of WFH are associated with substantial drops in commuting time, and reductions are larger for women than men. Taking into account Australian workers’ reported WFH preferences, our results suggest maximum potential future commuting time savings of about 17–25% compared to 2019.“ (authors’ abstract; BIBB-Doku)

„Führt Homeoffice zu Einsparungen der wöchentlichen Pendelzeit? Die Reduktion von Pendelzeiten wird häufig als ein zentraler Vorteil von Homeoffice genannt. Doch inwiefern trifft dies überhaupt zu? Und welche Rolle spielen dabei das Ausmaß und wie lange schon im Homeoffice gearbeitet wird?“ (BIBB-Doku)
Keywords: G 2.3.3 Arbeitsformen, Techniken; G 1.3.3.3 Mobilität; I 2.3.5 Australien, Ozeanien; 370; 330; Telearbeit; Einflussfaktor; Mobilität; Mobilitätsforschung; Zeit und Beruf; Zeitverwendung; Australien; 2002-2019